Green synthesis of silver and copper nanoparticles and their composites using Ocimum sanctum leaf extract displayed enhanced antibacterial, antioxidant and anticancer potentials - M. Ashokkumar; K. Palanisamy; A. Ganesh Kumar; C. Muthusamy; K. J. Senthil Kumar (Artificial Cells, Nanomedicine, and Biotechnology)
Green-synthesized silver and copper nanoparticles (NPs), along with their composites, exhibit various biological activities. Ocimum sanctum (Holy basil), traditionally used as medicine in South Asia, treats respiratory disorders, digestive issues, skin diseases and inflammatory conditions. Modern scientific studies support these bioactivities; however, no studies have investigated their bioactivity in combination with NPs. In this study, silver and copper NPs were synthesized using AgNO3 and CuSO4·5H2O solutions, respectively, with Ocimum sanctum leaf extract, and their antibacterial, antioxidant and anticancer properties were examined. Spectroscopic analyses, including Fourier transform infra-red (FTIR), transmission electron microscopy (TEM) and X-ray diffraction (XRD), elucidated the physicochemical characteristics of the green-synthesized nanoparticles (Os-AgNPs and Os-CuNPs), revealing sizes of 11.7 and 13.1 nm, respectively. The Os-AgNPs:Os-CuNPs nano-composite with a 1:2 ratio exhibited a zone of inhibition ranging from 8 to 12 mm against tested bacterial pathogens. Additionally, the NPs and their composites demonstrated potent antioxidant activity, with notable 2-diphenyl-2-picrylhydrazyl (DPPH) scavenging activity observed in composites with ratios of 2:1 and 1:2. Furthermore, they displayed potential anticancer activity against human leukaemia (Jurkat) cancer cells. Although no distinct difference in anticancer property was observed among the NPs and their composites, our study highlights their well-defined nanostructure and significant biological activity, suggesting their potential as therapeutic agents in the pharmaceutical industry.